Dirac Fermions: Fermi Velocity Reduction of Dirac Fermions around the Brillouin Zone Center in In2Se3–Bilayer Graphene Heterostructures (Adv. Mater. 17/2021). Issue 17 (27th April 2021) - Wang, Zhenyu; Hao, Zhanyang; Yu, Yayun; Wang, Yuan; Kumar, Shiv; Xie, Xiangnan; Tong, Mingyu; Deng, Ke; Hao, Yu‐Jie; Ma, Xiao‐Ming; Zhang, Ke; Liu, Cai; et al.
Abstract : In article number 2007503, Zhenyu Wang, Jianfeng Wang, Chaoyu Chen, and co‐workers develop a practical strategy to construct moiré Dirac cones around the Brillouin zone center by folding graphene Dirac cones in monolayer In2 Se3 /bilayer graphene heterostructures. The Fermi velocity of the moiré Dirac cones is reduced by ≈23%, and the reshaped Dirac point at the Γ point is elongated. Both features further confirm moiré Dirac fermion renormalization and interactions.